The Impact of Fresh Hass Avocado on the Fecal Metabolome Among Adults with Overweight and Obesity: A Randomized, Controlled Trial - Thompson, Sharon (Curr Dev Nutr, 2020)
OBJECTIVES: Avocados are nutrient-rich fruits that have been recently linked to beneficial alterations to the gastrointestinal microbiota. However, previous research on shifts in the fecal metabolome with avocado intake has largely been conducted in in vitro or preclinical models and little is known about their metabolomic impact in human subjects. METHODS: Adult participants (n = 109) 25–45 years of age with BMI ≥ 25.0 kg/m(2) were enrolled in an investigator-blinded, parallel arm, randomized, controlled trial. Participants consumed isocaloric meals with or without fresh Hass avocado once daily for 12-weeks and reported ≥ 80% meal consumption over the intervention period. Untargeted fecal metabolites were quantified in a subsample of participants (n = 48) using gas chromatography mass spectroscopy and were normalized by sample weight. Kruskal-Wallis tests and false discovery rate type I error correction were conducted and orthogonal partial least squares discriminant analysis (OPLS-DA) was used to predict treatment group by fecal metabolite concentrations (RStudio, version 3.6.2). RESULTS: A total of 292 metabolites were identified at intervention follow-up. Of these, three metabolites differed significantly between treatment groups. Fecal concentrations of lanosterol (P = 0.0004, q = 0.04) and the fatty alcohols hexadecanol (P = 0.001, q = 0.04) and octadecanol (P = 0.001, q = 0.04), were greater in the group consuming avocado as compared to control. Seventeen additional metabolites, including nine fecal lipids, two fat soluble vitamin derivatives, and three monosaccharides/disaccharides differed at P < 0.05 but did not meet the q < 0.05 threshold. Treatment group assignment was predicted correctly in 70% of cases (R(2 )= 72%, Q(2 )= 33%) using the trained OPLS-DA model. CONCLUSIONS: Fresh Hass avocado intake increased fecal lipid and sterol concentrations among healthy adults with overweight and obesity, demonstrating diet-related modifications to the fecal metabolome. FUNDING SOURCES: Support for this research was provided by the Hass Avocado Board, the USDA National Institute of Food and Agriculture, Hatch project 1009249, and the USDA National Institute of Food and Agriculture AFRI Predoctoral Fellowship, project 2018–07785.